Strategic planning in educational institutions, a useful tool to guarantee continuity - Núñez Esqueda, Claudia Verónica (Rastros Rostros, 2023)
Strategic planning is a tool capable of helping all organizations to maintain their productivity through their ability to adapt, both to market demand and to needs of the organization. Educational Institutions can also use it to achieve their objectives; specifically at the Villa de Matel High School, although strategic planning is not a well-defined program in all its areas and levels, it does have the necessary elements to develop it effectively. This document points out a brief analysis of the High School focused on the aforementioned mechanism and the resources that comprise it, likewise, a theoretical reference is included to give context and, in addition, the result of the swot analysis made to the Institution is specified, the suggestion for the use of 2 complementary tools to the planning and the corresponding conclusion; at the end of the writing are the bibliographical references.